Growth kinetic study of chlorella vulgaris using lab-scale and pilot-scale photobioreactor: Effect of CO2 concentration - Lam, M.K. (Taylor's University, 2016)
In the present study, growth kinetic of Chlorella vulgaris was performed when the microalgae was cultivated with different concentrations of CO2. The experiments were carried out using lab-scale and pilot-scale photobioreactors, and the growth results were analyzed using POLYMATH 6.0 with different growth kinetic models. The growth of the microalgae was found fitted well to the Richards growth model with attainable high R2 values as demonstrated in all studied cases, in concert with low values of root mean squares deviation (RMSD) and variance. In addition, the output from the plots of experimental values versus predicted values and residual plots further confirmed the good fit of Richards model. The predicted specific growth rate from Richards model was similar to the experimental specific growth rate with deviation lesser than 5. The attained results paved a preliminary prediction of microalgae growth characteristic when the cultivation is scaled-up to commercial scale. Â© School of Engineering, Taylorâs University.